Problem-based learning and the development of critical thinking skills - López Ayala, Juan Manuel (2020)
This text is part of a research paper called: "The influence of ABP on the development of critical thinking skills." Taking into consideration the main foundations established by Barrows (1982) regarding the ABP methodology, this pedagogical practice is introduced as a means to promote PC skills in higher education students. Likewise, the text serves as a reference for the teaching community in its search for the application of new active learning strategies that generate in its students formative aspects of a socio-critical nature with respect to their environment.